Introduction to research using subject indexes from Wilson. ([New York] H.W. Wilson, 1991)
Subject indexes are the most effective ways of locating precise, current and authoritative sources. This program shows the modern tools of information gathering, especially periodicals indexes in CD-ROMS of Wilson.
VHS
Keywords: Periodicals -- Indexes -- Data bases; Library science